Marketing of sheep in Sudan: an economic analysis - Mohamed Arshad, Fatimah; Ismail, Mohd Mansor; Elbadawi, Elsedig (LAP Lambert Academic Publishing, 2014)
Sudan is one of the largest exporters of sheep in Africa. However, the sheep marketing is still undeveloped due to lack of infrastructures such as extension services, roads and telecommunication, market information system, R&D and logistical supports. One of the major policy instruments that discourage innovations is the imposition of direct taxes on the producers and marketers at all level of marketing chains. This book aims to provide some insights on the marketing system of sheep in Sudan with a special focus on the production sector in the North Kordofan, Gadarif and Khartoum states in Sudan. Specifically, it intends to; (i) provide a better understanding of the existing sheep marketing system, (ii) identify key constraints and potentials, (iii) describe the marketing channels and margins and; (iv) measure the competitiveness and comparative advantage of the sheep industry using policy analysis matrix (PAM) framework. Based on the findings, this book recommend that there is a need to reorganize and shorten the marketing channel, to institute a price support for the supply of fodder, provide water and veterinary care, and waive income taxes on the farmers and traders.